The Sustainable Territorial Innovation of “Inner Peripheries”. The Lazio Region (Italy) Case - Battaglini, Elena (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
This methodological, policy-focused paper firstly defines the concept of “sustainable territorial innovation” and its operationalisation according to the strategic objectives of Europe 2020. Statistical processing was based on 26 indicators, which helped to perform a multivariate analysis and allowed to identify ten groups of municipalities characterised in terms of the territorial sustainable innovation idea. Their GIS spatial distribution has led authors to combine them with the set of indicators proposed by the Italian Government in the UE Cohesion Policy 2014–2020 perspective. The paper also addresses the constraints and opportunities for urban and peri-urban policies within new scenarios.